1977
DOI: 10.1161/01.str.8.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Experimental regional cerebral ischemia in the middle cerebral artery territory in primates. Part 1: Angio-anatomy and description of an experimental model with selective embolization of the internal carotid artery bifurcation.

Abstract: SUMMARY Selective embolization of the internal carotid artery bifurcation (ICA bifurcation) was performed in monkeys (Macaca mulatto) to study acute regional cerebral ischemia in the middle cerebral artery (MCA) territory with minimum surgical intervention in the neck under sedated conditions.The anthropomorphic similarity in angio-anatomy of the carotid system of monkeys and the use of silastic spheres, as artificial emboli, of the critical diameter of 1.2 to 1.4 mm resulted in the overall success rate of 87%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 25 publications
(13 reference statements)
1
18
0
2
Order By: Relevance
“…In other models in which in situ perfusion fixation was reportedly employed following MCA interruption or occlusion by several different methods, the effect of MCA occlusion on the dependent vascular bed was not examined. 26 - 21 The failure to observe occlusive material in perforating vessels in the regions of a lenticulostriate artery-dependent cerebral infarction in various primate models when specimens were prepared remotely after stroke induction may be explained by active endogenous fibrinolysis of occlusive thrombi within these small vessels within hours of thrombus formation as recently demonstrated for acute thrombotic occlusion during myocardial infarction. 34 Previous morphologic studies employing in situ perfusion fixation have been inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…In other models in which in situ perfusion fixation was reportedly employed following MCA interruption or occlusion by several different methods, the effect of MCA occlusion on the dependent vascular bed was not examined. 26 - 21 The failure to observe occlusive material in perforating vessels in the regions of a lenticulostriate artery-dependent cerebral infarction in various primate models when specimens were prepared remotely after stroke induction may be explained by active endogenous fibrinolysis of occlusive thrombi within these small vessels within hours of thrombus formation as recently demonstrated for acute thrombotic occlusion during myocardial infarction. 34 Previous morphologic studies employing in situ perfusion fixation have been inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…7 -* The orbitofrontal artery is a prominent cortical vessel in the baboon and is often found within a few mm of the middle cerebral artery bifurcation. Watanabe 7 and Laurent et al* reported that the LLS arteries of the baboon most often arise as a cluster of vessels directly from the orbito-frontal artery. We have observed this occurrence in 6 of the 14 examined middle cerebral arteries (10 surgical observations and 4 postmortem following the injection of silicone rubber).…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…We examined the temporal and regional pattern of neuronal apoptosis, as well as NFKB activation in this experimental transient focal ischemia in rats (1-hour ischemia with desired time interval for reperfusion) using the mono-filament model [48].…”
Section: Resultsmentioning
confidence: 99%
“…Exposiure to aE2 can activate the MAP kinase pathway (47), and this pathway is implicated in /3E2-mediated neuroprotection (14). In addition, aE2 has also been shown to have several other direct effects on nexu"ons, including modulation of the mitochondrial Na-f/K"^-ATPase activity (48), alteration of membrane fluidity (49), and inhibition of toxin-induced activation of NFKB (P. S. Green and J. W. Simpkins, xmpublished observations). It is unknown whether Ent-Ej can also interact with any of these cellular pathways.…”
Section: Ent-e2 ■Pe2mentioning
confidence: 99%